Diverse teams researching diversity: Negotiating identity, place and embodiment in qualitative research. (February 2023) - Mathijssen, Brenda; McNally, Danny; Dogra, Sufyan; Maddrell, Avril; Beebeejaun, Yasminah; McClymont, Katie
Fieldwork encounters are not only contingent to biographical subjectivities, but are mediated by a confluence of identity, place and embodiment. This paper offers reflexive accounts of researchers with various socio-cultural and disciplinary backgrounds, who collaborated as a team to examine the varied funerary experiences and needs of established minorities and recent migrants in England and Wales. Focusing on the researchers' varied personal experiences with death and bereavement and on their performances of minority and majority ethnic and migrant identities, the paper highlights the mediated and embodied nature of fieldwork. It argues that reflection on the various aspects of intersectional researcher identity is necessary for a rigorous fieldwork practice that takes transparency and politics into account. This facilitates a deeper understanding of the positionality of both researchers and interlocutors, and the situated co-production of knowledge. In doing so, the paper illustrates that conducting research with a diverse team of researchers contributes to better understanding the complexity and multifacetedness of social phenomena.